Mild Hypobaric Hypoxia Enhances Post-exercise Vascular Responses in Young Male Runners - Saito, Yoko; Nakamura, Mariko; Eguchi, Kazumi; Otsuki, Takeshi (Frontiers in Physiology, 2019)
It has been reported that sustained post-exercise vasodilation may be linked to exercise-induced angiogenesis. The present study aimed to evaluate whether mild hypobaric hypoxia enhances the post-exercise reduction in systemic vascular resistance in young male runners. Seven male intercollegiate runners (aged 19–21 years) performed maximal incremental treadmill running under conditions of hypobaric hypoxia (corresponding to 2,200 m above sea level, hereinafter referred to as HH) and normobaric normoxia (corresponding to sea level, hereinafter referred to as NN). A third exercise test was performed under NN conditions, consisting of submaximal exercise with the same absolute exercise volume as was achieved during HH (submaximal exercise under NN conditions, hereinafter referred to as NNsubmax). Blood pressure and cardiac output (CO) were measured before and at 15, 30, and 60 (p60) minutes after exercise. Compared with NN, exercise time was shorter in HH and NNsubmax conditions (p < 0.05). Systolic blood pressure and mean blood pressure (MBP) were lower after exercise in HH conditions (p < 0.05). No condition-related differences were found in CO. Total peripheral resistance (TPR, defined as the ratio of MBP to CO) was significantly lower after exercise compared to baseline for all conditions (p < 0.05). However, the decrease in TPR was maintained longer after exercise in HH compared with NN and NNsubmax conditions (p < 0.05). At p60, TPR was lower than baseline for HH conditions (p < 0.05), whereas after exercise in NN, and NNsubmax conditions, TPR recovered to baseline by p60. Decreases in systemic vascular resistance after exercise were maintained longer under mild HH conditions compared with NN despite the lower exercise volume of the former.